Characterization of Tobacco Stem Biochar for Controlled Release Fertilizer at Varying Pyrolysis Conditions - Prasiefa, Mizanurafi' Ghifarhadi; Firmansyah, Daniyal (Prodi Kimia, 2025)
The development of Controlled Release Fertilizer (CRF) aims to reduce nutrient losses and environmental pollution caused by the rapid nutrient release from conventional fertilizers, which can result in 40%–90% NPK loss. This study focuses on producing tobacco stem biochar (TSB) through pyrolysis of tobacco stem powder to support CRF applications. The objective is to determine the optimal pyrolysis condition that yields TSB with properties suitable for land remediation and enhanced plant growth. Tobacco stem powder was subjected to pyrolysis under varying conditions, with TSB-3—produced at 600°C for 1 hour and an average heating rate of 30°C/min—emerging as the most efficient. This variant achieved a 28.99% mass yield, 73.09% fixed carbon, 77.47% porosity, 521.81 m²/g surface area, and 555.68 microns particle size. Additionally, it had a pH of 9.51, 24.18% nitrogen, 2.1% phosphorus, 1.8% potassium, 8.499 meq/100g CEC, 0.323 dS/m EC, and a salt index of 2.58. Enzymatic activities included 2.47 µmol/mL/min urease, 1.89 µmol/mL/min phosphatase, and 48.1 µmol/mL/min dehydrogenase. These results suggest TSB-3 is a promising candidate for nutrient carrier in CRF formulation, contributing to sustainable agriculture through improved nutrient use efficiency and soil health enhancement.